Prevalence of prostate cancer in three cancer prevention campaigns in Montes Claros, Minas Gerais, Brazil - Rodrigues Aguiar de Carvalho, Jaqueline; Katherine Rodrigues, Raíssa (Revista Unimontes Científica, 2020)
Casos novos de câncer de próstata detectados em um mutirão Abstract: Objective: To investigate the prevalence of prostate cancer in the population attended in the 6th, 7th, and 8th Cancer Prevention Campaigns held in the city of Montes Claros, in the state of Minas Gerais, Brazil. Methodology: This is an epidemiological descriptive prevalence study. Data were collected from patients attending the Urology Tent in the Cancer Prevention Campaigns conducted from 2016 to 2018. Results: The sample consisted of 1,554 ind ividuals, most of which were in 60-69 years old. In 2016, 481 men were attended, 37% of which have never been submitted to rectal examination, with altered results for this exam in 23.6% of the cases. In 2017, from 501 men, 25.5% have never had rectal examination, with altered results for this exam in 21.6% of the cases. In 2018, 572 men were attended, 61.0% of which have never been submitted to rectal examination, with altered results for this exam in 9.3% of the cases. Conclusion: In 2016, 13 cases of prostate cancer were confirmed. In 2017, 6 cases were diagnosed, and in 2018 there were 17 cases, amounting to 36 cases of prostate cancer. Resumo: Objetivo: Verificar a prevalência do câncer de próstata na população assistida nos 6º, 7º e 8º Mutirões de Prevenção ao Câncer, realizado na cidade de Montes Claros – MG. Metodologia: Trata-se de um estudo epidemiológico de prevalência descritivo. Foram analisados dados obtidos em atendimentos realizados na tenda da urologia dos Mutirões de Prevenção ao Câncer – realizados pela Associação Presente, nos anos de 2016 a 2018. Resultados: A amostra foi composta por 1554 indivíduos, a maioria se encontrava na faixa etária de 60-69 anos. No ano de 2016 foram atendidos 481 homes, 37% nunca haviam realizado toque retal, e o exame foi considerado anormal em 23,6% dos casos. No ano de 2017 de 501 homens, 25,5% nunca haviam realizado toque retal, e o exame foi considerado anormal em 21,6% dos casos. No ano de 2018 foram atendidos 572 homens, 61,0% nunca haviam realizado toque retal, e o exame foi considerado anormal em 9,3% dos casos. Conclusão: No ano de 2016, foram confirmados 13 casos de câncer de próstata. No ano de 2017, foram diagnosticados 6 casos e no ano de 2018 foram 17 casos, correspondendo a um total de 36 casos de câncer de próstata.